INTERCONNECTION BETWEEN STUDENT’S PREREQUISITE COURSES ACHIEVEMENT AND SUBSEQUENT ACHIEVEMENT IN MECHANICS - K, Caca Candra; Wahyuni, Agus; Syukri, Muhammad (Jurnal Pengajaran MIPA, 2018)
This study investigated the interconnection between student’s achievements in prerequisite courses with their subsequent achievement in mechanics. Eighty-five preservice physics students’ achievement in four prerequisite courses for mechanics, namely Basic Physics I, Basic Physics II, Mathematics Physics I, and Mathematics Physics II, were analyzed statistically to determine the relationships and effects of prior achievement to sub-sequent learning achievement. Results suggested that students’ achievement in mechanics was significantly re-lated to students’ achievement in prerequisite courses. The effects of each course on student’s achievement in mechanics were estimated and discussed.